Zn diffusion and reflow behaviour of Sn-9Zn and Sn-8.5Zn-0.5Ag-0.01Al-0.1Ga solders on a Ni/Cu substrate under IR reflow. Issue 2 (1st April 2014) - Mittal, J.; Lin, K.L.
Abstract : Purpose: – This paper aims to compare the reflow and Zn diffusion behaviors in Sn-Zn and Sn-8.5Zn-0.5Ag-0.01Al-0.1Ga (5E) solders during soldering on a Ni/Cu substrate under infrared (IR) reflow. The study proposes a model on the effect of various elements particularly Zn diffusion behavior in the solders on the formation of intermetallic compounds (IMCs). Design/methodology/approach: – The melting activities of two solders near their melting points on copper substrates are visualized in an IR reflow furnace. Reflowed solder joints were analyzed using scanning electron microscope and energy dispersive X-ray spectroscopy. Findings: – Reflow behaviors of the solders are similar. During melting, solder balls are first merged into each other and then reflow on the substrate from top to bottom. Both solders show a reduced amount of Zn in the solder. Theoretical calculations demonstrate a higher Zn diffusion in the 5E solder; however, the amount of Zn actually observed at the solder/substrate interface is lower than Sn-9Zn solder due to the formation of ZnAg3 in the solder. A thinner IMC layer is formed at the interface in the 5E solder than the Sn-Zn solder. Research limitations/implications: – The present work compares the 5E solder only with Sn-Zn solder. Additional research work may be required to compare 5E solder with other solders like Sn-Ag, SnAgCu, etc. to further establish its practical applications. Practical implications: – The study ascertains the advantages of 5E solder over Sn-Zn solder for all practical applications. Originality/value: – The significance of this paper is the understanding of the relation between reflow behavior of solders and reactivity of different elements in the solder alloys and substrate to form various IMCs and their influence on the formation of IMC layer at solder/substrate interface. Emphasis is provided for the diffusion behavior of Zn during reflow and respective reaction mechanisms.